Kestävyyskunnon, fyysisen aktiivisuuden, voimaharjoittelun ja paikallaanolon yhteydet insuliiniresistenssiin 15–17-vuotiailla nuorilla - Laaksonen, Heikki (2024)
ABSTRACT Laaksonen, H. 2024. Associations of cardiorespiratory fitness, physical activity, strength training and sedentary behavior to insulin resistance in adolescents aged 15–17 years. Faculty of Sport and Health Sciences, University of Jyväskylä, master’s thesis in Sports and Exercise Medicine, 70 pp.